2018
DOI: 10.2214/ajr.17.18309
|View full text |Cite
|
Sign up to set email alerts
|

Segmental Arterial Mediolysis: Abdominal Imaging of and Disease Course in 111 Patients

Abstract: SAM most commonly affects the renal arteries, superior mesenteric artery, and celiac artery. Dissections and aneurysms are the most common imaging findings. Follow-up imaging studies show stability or regression in most patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
74
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 48 publications
(78 citation statements)
references
References 23 publications
2
74
0
Order By: Relevance
“…Various etiological factors for SAA have been reported, including angiodysplasia [6], segmental arterial mediolysis [18], portal hypertension [6,8], pregnant or multiparous woman [4,6], atherosclerosis [6,8], essential hypertension [8,19], diabetes mellitus [19], syphilis [6], intracranial aneurysm [19], embolic diseases [6], polyarteritis nodosa [19], α1-antitrypsin deficiency [20], and infective factors and inflammation [6,8]. Interestingly, although the SAA in this case had severe calcification, the pathology evaluation revealed no atherosclerotic changes.…”
Section: Discussionmentioning
confidence: 99%
“…Various etiological factors for SAA have been reported, including angiodysplasia [6], segmental arterial mediolysis [18], portal hypertension [6,8], pregnant or multiparous woman [4,6], atherosclerosis [6,8], essential hypertension [8,19], diabetes mellitus [19], syphilis [6], intracranial aneurysm [19], embolic diseases [6], polyarteritis nodosa [19], α1-antitrypsin deficiency [20], and infective factors and inflammation [6,8]. Interestingly, although the SAA in this case had severe calcification, the pathology evaluation revealed no atherosclerotic changes.…”
Section: Discussionmentioning
confidence: 99%
“… 8 , 9 Commonly affected vascular territories are the celiac, mesenteric, and renal arteries, although central nervous system presentations have also been reported. 10 , 11 Epidemiological data indicate that there is a slight male preponderance, with presentation typically between the fifth to sixth decades of life. 10 However, as patients may sustain silent infarcts or have asymptomatic disease progression, SAM may in fact have an earlier age of onset.…”
Section: Discussionmentioning
confidence: 99%
“… 10 , 11 Epidemiological data indicate that there is a slight male preponderance, with presentation typically between the fifth to sixth decades of life. 10 However, as patients may sustain silent infarcts or have asymptomatic disease progression, SAM may in fact have an earlier age of onset. Presentations of SAM vary depending on the affected vascular territories, as well as the extent of involvement.…”
Section: Discussionmentioning
confidence: 99%
“…Arterial dissections account for the majority of the reported cases of SAM, followed by pseudoaneurysms. When dissection of peripheral arteries unrelated to the aorta is observed, a diagnosis of SAM should be considered [5,7,8].…”
Section: Discussionmentioning
confidence: 99%
“…Naidu et al [8] and Michael et al [9] have shown that CTA provides the spatial resolution and vessel detail required for the acute diagnosis of SAM. Serial CTA is found to be superior to conventional angiography, as it able to evaluate perivascular inflammation, vessel wall thickening, and rapidly evolving lesions [9].…”
Section: Discussionmentioning
confidence: 99%